Thin-Slice Forecasts of Gubernatorial Elections - Benjamin, Daniel J; Shapiro, Jesse M (The Review of Economics and Statistics, 2009)
We showed 10-second, silent video clips of unfamiliar gubernatorial debates to a group of experimental participants and asked them to predict the election outcomes. The participants' predictions explain more than 20 percent of the variation in the actual two-party vote share across the 58 elections in our study, and their importance survives a range of controls, including state fixed effects. In a horse race of alternative forecasting models, participants' forecasts significantly outperform economic variables in predicting vote shares, and are comparable in predictive power to a measure of incumbency status. Participants' forecasts seem to rest on judgments of candidates' personal attributes (such as likeability), rather than inferences about candidates' policy positions. Though conclusive causal inference is not possible in our context, our findings may be seen as suggestive evidence of a causal effect of candidate appeal on election outcomes.